BECAUSE MOTIVE AHBAB: A PHENOMENOLOGICAL ANALYSIS OF AHBAB TABLIGHI JAMA’AT DA’WAH MOVEMENT - Ilal Ilham; Tresno Tresno; Muhammad Rifai; Gunawan Gunawan; Mallia Hartani; Suci Wahyu Fajriani (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This article discusses a phenomenological study of Tablighi Jama’at ahbab, focusing on the motives of Tablighi Jama’at ahbab. The purpose of this study is to explore the subjective experiences and unconscious motives of ahbab participating in the Tablighi Jama’at da'wah movement. This study uses a qualitative approach with an exploratory descriptive research type that aims to describe and explore the phenomenon in depth. The data collection techniques in this study used participant observation to directly observe experiences in the field and in-depth interviews to understand the perspectives of the ahbab. In determining the research informants, the author used purposive sampling techniques, and the data obtained was analysed using Miles and Huberman's data analysis. The results of the study show that the reasons for ahbab joining Tablighi Jama’at are: wanting to experience the atmosphere of their previous environment, practising what they have learned, because Tablighi Jama’at does not question specific schools of thought and sects, the approach of Tablighi Jama’at as a means of learning Islam, finding something different in Tablighi Jama’at, protection within Tablighi Jama’at, and because Tablighi Jama’at does not differentiate between ahbab and the redemption of sins. These findings provide an understanding of various factors that motivate people to join a religious movement.